Insights into crystallization and melting of high density polyethylene/graphene nanocomposites studied by fast scanning calorimetry. (May 2018) - Tarani, E.; Papageorgiou, D.G.; Valles, C.; Wurm, A.; Terzopoulou, Z.; Bikiaris, D.N.; Schick, C.; Chrissafis, K.; Vourlias, G.
Abstract: Graphene nanoplatelets (5 wt%) with different diameters (5 and 25 × 10 −6  m in diameter, 6 × 10 −9  m in thickness) filled high density polyethylene nanocomposites were prepared by the melt-mixing method and the effect of graphene nanoplatelets on the polymeric matrix are then investigated by X-ray diffraction, polarized light microscopy, differential scanning calorimetry, fast scanning calorimetry, and rheology. Polarized light microscopy revealed that graphene nanoplatelets of 5 × 10 −6  m promote the decrease in the size of the spherical aggregates during crystallization compared to larger nanoplatelets. From rheological measurements, it was found that even though the viscosity of the nanocomposites with increasing filler diameter was increased significantly compared to the neat polymer, the processability of these materials was not affected. Several melting events for neat high-density polyethylene and graphene nanocomposites were observed by fast scanning calorimetry associated with the small imperfect crystals grown at large supercooling, the nucleation efficiency and the diameter size of the filler. The activation energy values versus the relative extent of crystallization revealed that graphene nanoplatelets block the movement of the molecular segments and make crystallization difficult, especially at the final stage of the process. Based on this work, it can be concluded that the nanocomposite with the smaller diameter showed the most enhanced crystallization kinetics as graphene increased the number of nucleation sites, while the larger ones hindered the melted molecules in reaching full isotropization above the melting temperature. Highlights: Higher storage and loss moduli of nanocomposites are evidence that graphene nanoplatelets form a network in the matrix. The polymer chain relaxation and the relative motion have significantly been restrained adding graphene nanoplatelets. Several melting events for neat HDPE and the graphene nanocomposites were observed by fast scanning calorimetry. The melting events were associated with the large nucleation density of graphene nanoplatelets. Graphene nanoplatelets make the crystallization to be difficult, especially at the final stage of the process.